Marmoset model of trauma-induced epileptogenesis. Issue 8 (August 2019) - Bukhtiyarova, Olga; Timofeev, Igor
Abstract : We investigated brain electrographic activity in freely behaving marmosets before and after cortical penetrating wound. Based on visual examination of the multi-channel cortical and hippocampal LFP recordings and muscle activity, we were able to distinguish six behavioural states: active and quiet wake, an intermediate state, NREM2, SWS and REM sleep. We developed a procedure for automatic classification of states of vigilance in marmosets based on different LFP power bands and muscle tone with the use of self-organizing maps. Marmosets were typically awake during the day with few occasional naps and had 12–18 sleep cycles during night. In order to evaluate them as a model of human trauma-induced epileptogenesis, we produced cortical penetrating wound in 3 marmosets. All of them developed electrographic epileptiform activity within the first weeks that was primarily local. Its secondary generalization led to behavioural seizures that started to manifest 2–4 weeks after the onset of electrographic events. Conclusion: Cortical penetrating wounds in marmosets trigger epileptogenesis that result in seizure onset within a few weeks. Their brain state cycle is closer to human as compared to typical laboratory animals (rodents and carnivores) that favours translation of findings in marmoset model of trauma-induced epileptogenesis to human studies. Supported by CIHR and Savoy Foundation.